2017
DOI: 10.1001/jamacardio.2016.3234
|View full text |Cite
|
Sign up to set email alerts
|

Resting Heart Rate and Long-term Outcomes Among the African American Population

Abstract: Importance Increased resting heart rate is associated with worse outcomes in studies of mostly white populations, but its significance is not well established in African Americans whose cardiac comorbidities and structural abnormalities differ. Objective We studied the prognostic utility of heart rate in a community-based African American cohort in Jackson, Mississippi. Design We included 5261 participants in the Jackson Heart Study. Baseline heart rate was assessed by quintiles and as a continuous variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…bisoprolol) in African Americans: A subgroup analysis of 207 Black patients in the Metoprolol CR/XL Randomized Intervention trial in Congestive Heart Failure (MERIT-HF) found no significant differences for various outcomes of all-cause and CV-related death (p > 0.05 for all). 31 Furthermore, direct comparisons of BBs to other therapies such as hydralazine/ISDN in African Americans would provide more evidence and guidance for place in therapy of BBs.…”
Section: Review Of Notable Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…bisoprolol) in African Americans: A subgroup analysis of 207 Black patients in the Metoprolol CR/XL Randomized Intervention trial in Congestive Heart Failure (MERIT-HF) found no significant differences for various outcomes of all-cause and CV-related death (p > 0.05 for all). 31 Furthermore, direct comparisons of BBs to other therapies such as hydralazine/ISDN in African Americans would provide more evidence and guidance for place in therapy of BBs.…”
Section: Review Of Notable Clinical Trialsmentioning
confidence: 99%
“…25,26 The earlier Jackson Heart Study found that elevated heart rate is associated with increased HF hospitalizations in African Americans, thus conferring an even greater necessity to evaluate the clinical utility of nonbeta-blocking agents, particularly ivabradine. 31 Considering the ambiguity of beta-blocker benefit to African American HF r EF patients as seen in the BEST Trial, further evaluation of alternate mechanisms of ventricular rate reduction is especially warranted in this population. Further evaluation of these rate-reducing agents is vital to the clinical understanding of reducing hospitalizations, improving symptomology, and enhancing quality of life in African American HF r EF patients, especially in patients with sustained elevated heart rate despite optimal beta-blocker therapy.…”
Section: Review Of Notable Clinical Trialsmentioning
confidence: 99%
“…Heart rate (HR) is an easily measured and modifiable clinical parameter. Previous studies have demonstrated that HR was an independent risk factor for total and cardiovascular (CV) mortality in general population as well as in patients with CV disease [ 1 5 ]. In a post hoc analysis of the Platelet Glycoprotein IIb-IIIa in Unstable Angina: Receptor Suppression Using Integrilin Therapy (PURSUIT) trial, elevated HR was associated with 30-day death among patients with non-ST-segment elevation myocardial infarction (MI) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher RHR is associated with higher levels of oxidative stress, endothelial dysfunction and atheromatous plaque formation 12. Previous studies conducted in mainly Western populations have reported conflicting results, both qualitatively and quantitatively, about the associations of RHR with HF,13–16 with some studies reporting J-shaped associations between RHR and HF 15 16. It is unclear the extent to which the associations of RHR with HF may be an artefact of incomplete adjustment for confounding by established risk factors, reverse causality or both.…”
Section: Introductionmentioning
confidence: 99%